2013
DOI: 10.1021/cm400129z
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Atomistic Simulations, and Phase Transition of Stoichiometric Yeelimite

Abstract: Yeelimite, Ca 4 [Al 6 O 12 ]SO 4 , is outstanding as an aluminate sodalite, being the framework of these type of materials flexible and dependent on ion sizes and anion ordering/disordering. On the other hand, yeelimite is also important from an applied perspective as it is the most important phase in calcium sulfoaluminate cements. However, its crystal structure is not well studied. Here, we characterize the room temperature crystal structure of stoichiometric yeelimite through joint Rietveld refinement usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
130
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 55 publications
(78 reference statements)
12
130
0
Order By: Relevance
“…The ACn content of this CSA cement,~15 wt.%, is slightly higher than that found for OPC cements,~10 wt.% [41,42], likely due to the lower clinkering temperature leading to smaller particle sizes and microstrains and defects-bearing crystals. The crystal structure descriptions for each phase were those detailed elsewhere [15], except for ye'elimite, where a reviewed orthorhombic C 4 A 3 S has been used [43]. The ACn content in FA is~85 wt.%, where mullite and quartz and some other crystalline minor phases (hematites, magnesium-ferrite, lime and periclase) are also present as crystalline fraction.…”
Section: Compressive Strengthsmentioning
confidence: 99%
“…The ACn content of this CSA cement,~15 wt.%, is slightly higher than that found for OPC cements,~10 wt.% [41,42], likely due to the lower clinkering temperature leading to smaller particle sizes and microstrains and defects-bearing crystals. The crystal structure descriptions for each phase were those detailed elsewhere [15], except for ye'elimite, where a reviewed orthorhombic C 4 A 3 S has been used [43]. The ACn content in FA is~85 wt.%, where mullite and quartz and some other crystalline minor phases (hematites, magnesium-ferrite, lime and periclase) are also present as crystalline fraction.…”
Section: Compressive Strengthsmentioning
confidence: 99%
“…The general formula refers to a structure that is (ideally) a body-centered cubic unit cell with a lattice parameter of 9 Å and where M is a relatively lowcharged caged cation such as Ca, Na or Sr 2 ; T occupies tetrahedral site(s) and is typically Si or Al; and X is the looselybonded caged anion which is either spherical (in the case of Cl) or tetrahedral (in the case of SO 4 , WO 4 , and CrO 4 ). Sodalites are interesting materials for several reasons such as their ferroic phase transition 3 from the high-temperature cubic phase to complex superstructures at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Stoichiometric calcium sulfoaluminate or ye'elimite, Ca 4 [Al 6 O 12 ]SO 4 , can be described as a sodalite where M = Ca, T = Al, and X =SO 4 , and crystallizes as a tectoaluminosilicate sodalite structure 4 . This structure was first analyzed by Hanstead and Moore 5 using X-ray powder diffraction, 6 and Saalfeld and Depmeier 7 reported atomic parameters for a cubic crystal structure with space group I ̅ 3m and a=9.195 Å.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hargis et al refined the three crystal systems separately by Rietveld refinement and showed that the fitting result of the orthorhombic is the best [11]. Cuesta et al indicated that CSA mineral could be orthorhombic and that orthorhombic crystal sometimes would transform into the cubic at around 470 °C [12,13]. Andac et al also showed that crystal system transition occurred at around 470 °C [14].…”
Section: Introductionmentioning
confidence: 99%